2020
DOI: 10.1182/blood.2020007145
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated myeloid cells provide critical support for T-ALL

Abstract: Despite harboring mutations in oncogenes and tumor suppressors that promote cancer growth, T-cell acute lymphoblastic leukemia (T-ALL) cells require exogenous cells or signals to survive in culture. We previously reported that myeloid cells, particularly dendritic cells (DCs), from the thymic tumor microenvironment (TME) support the survival and proliferation of primary mouse T-ALL cells in vitro. Thus, we hypothesized that tumor-associated myeloid cells would support T-ALL in vivo. Consistent with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 57 publications
5
38
1
Order By: Relevance
“…Surprisingly, dendritic cells were dispensable for leukemia progression in vivo. 1 This discrepancy with the previous report could be due to several reasons. First of all, the differences between in vitro and in vivo experimental systems could have an impact.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Surprisingly, dendritic cells were dispensable for leukemia progression in vivo. 1 This discrepancy with the previous report could be due to several reasons. First of all, the differences between in vitro and in vivo experimental systems could have an impact.…”
contrasting
confidence: 55%
“…
In this issue of Blood, Lyu et al tackle the fascinating question of identifying novel mediators of leukemia progression hidden in the intricate host environment. 1 Particularly, they provide robust evidence for an essential role of myeloid cells in supporting T-cell acute lymphoblastic leukemia (T-ALL).
…”
mentioning
confidence: 99%
“…M2 macrophages were also shown to provide pro-survival signals to T-ALL cells. Human macrophages cultured in vitro secreted insulin-like growth factor IGF1, which contributed to increased survival of T-ALL cells expressing IGF1-R (insulin-like growth factor 1 receptor) [104]. Accordingly, depletion of myeloid cells led to reduced leukemic burden and improved survival of mice in the LN3 transgenic model of T-ALL [104].…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 99%
“…Additionally, recent unbiased genome-wide profiling analyses have expanded our understanding of the genetic landscape of T-ALL, identifying novel driver genes and associated molecular mechanisms that promote leukemia initiation and progression (14). However, despite multiple pro-leukemic genomic lesions, T-ALL cells cannot survive in vitro in the absence of cytokines or supportive cell types (15,16), suggesting that cells or signals in the leukemia-microenvironment are required to support leukemia growth and could thus serve as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Several cell types in the TME have been shown to support T-ALL survival and progression, including vascular endothelial cells through a C-X-C motif chemokine receptor 4 (CXCR4)-CXCL12 axis in the BM (19,20), and thymic epithelial cells (TECs) through release of interleukin 7 (IL-7) and expression of NOTCH1 ligands (11,21,22). We have previously shown that tumor-associated myeloid cells provide critical support for T-ALL, in part by secreting IGF1 to activate IGF1R signaling in leukemic cells (15,16). However, IGF1 is not sufficient to support T-ALL survival in culture, and myeloid cells sensitize T-ALL cells to IGF1 (16), suggesting a role for additional molecular mechanisms underlying myeloid-mediated T-ALL support.…”
Section: Introductionmentioning
confidence: 99%